Coal mining meets chromatin research: Digging for mechanisms in epigenetic control of gene expression. (4th December 2012) - Ehrenhofer‐Murray, Ann; Meyer, Hemmo; Nellen, Wolfgang
Abstract Editor's suggested further reading in BioEssays Epigenetics meets mathematics: Towards a quantitative understanding of chromatin biologyAbstract